Antibiotic sensitivity pattern of Heamophilus species from infectious coryza in Namakkal - Prabhakar, T G; Dorairajan, N; Swaminathan, Raja; Sivakumar, S (The Indian Journal of Animal Sciences, 2012)
Haemophilus paragallinarum and Haemophtlus avum were isolated from birds having charactenstic symptoms of coryza. Haemophilus species were sensitive to enrofloxacin, ciprofloxacin and ampicillin and resistant to neomycin, cloxacillin, co-trimaxazole, lincomycin, caphalexin and amikacin.